Abnormal subgenual anterior cingulate circuitry is unique to women but not men with chronic pain. Issue 1 (January 2021) - Osborne, Natalie R.; Cheng, Joshua C.; Rogachov, Anton; Kim, Junseok Andrew; Hemington, Kasey S.; Bosma, Rachael L.; Inman, Robert D.; Davis, Karen D.
Abstract : Abstract: The subgenual anterior cingulate cortex (sgACC) plays an important role in pain modulation. We previously demonstrated sex differences in sgACC functional connectivity (FC) in healthy individuals. Given that many chronic pain conditions show sex differences in prevalence, here we tested the hypothesis that people with chronic pain exhibit a sex-specific pattern of abnormal sgACC FC. We acquired resting-state functional magnetic resonance imaging data from 156 (82 W: 74 M) healthy participants and 38 (19 W: 19 M) people with chronic low back pain resulting from ankylosing spondylitis, a condition that predominantly affects men. We confirmed that there are sex differences in sgACC FC in our large cohort of healthy adults; women had greater sgACC FC with the precuneus, a key node of the default mode network, and men had greater sgACC FC with the posterior insula and the operculum. Next, we identified an interaction effect between sex and pain status (healthy/chronic pain) for sgACC FC. Within the chronic pain group, women had greater sgACC FC than men to the default mode and sensorimotor networks. Compared to healthy women, women with chronic pain also had greater sgACC FC to the precuneus and lower FC to the hippocampus and frontal regions. No differences in sgACC FC were seen in men with vs without chronic pain. Our findings indicate that abnormal sgACC circuitry is unique to women but not men with ankylosing spondylitis-related chronic pain. These sex differences may impact the benefit of therapeutics that target the sgACC for chronic pain. Abstract : Supplemental Digital Content is Available in the Text.In chronic pain, there are sex differences and sex-specific abnormalities in the functional connectivity of the subgenual anterior cingulate cortex, a key node of the descending antinociceptive system.